2016
DOI: 10.1111/ssqu.12322
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of the “Two Souths?” Racial Resentment and White Party Identification in the Deep South and Rim South*

Abstract: Objectives This article addresses a debate among scholars of southern politics concerning the relevance of the distinction between the Deep South and Rim South states. Specifically, it examines the effect of racial resentment on white party identification in both southern subregions. Methods Data from the 2010 and 2012 Cooperative Congressional Election Studies (CCES) are analyzed using a multivariate logistic regression model to examine subregional differences in the effect of racial resentment on southern wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…2020). An extensive literature from the Obama Era validates the expectation that white racial conservatives expressed more negative views of the country's first black president and were more likely than other whites to oppose his agenda (e.g., Kinder and Dale‐Riddle 2012; Knuckey and Kim 2015, 2016; Knuckey 2016; Redlawsk, Tolbert, and Franko 2010; Tesler 2012). At the same time, several studies have cast doubt on the implicit priming theory (Bonilla, Filindra, and Lajevardi 2022; Newman et al.…”
Section: Literature Reviewmentioning
confidence: 85%
“…2020). An extensive literature from the Obama Era validates the expectation that white racial conservatives expressed more negative views of the country's first black president and were more likely than other whites to oppose his agenda (e.g., Kinder and Dale‐Riddle 2012; Knuckey and Kim 2015, 2016; Knuckey 2016; Redlawsk, Tolbert, and Franko 2010; Tesler 2012). At the same time, several studies have cast doubt on the implicit priming theory (Bonilla, Filindra, and Lajevardi 2022; Newman et al.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Following others (Leitner et al, 2018; Snowden & Michaels, 2022), only non‐Hispanic Whites' bias was assessed because African Americans' anti‐African American bias assesses what theorists consider “internalized racism” (Feldman & Huddy, 2005), which differs from White's anti‐African American bias. Other reasons to focus on Whites' tests include the centrality of anti‐African American belief to Whites' views of welfare (Davis & Wilson, 2021; Gilens, 2009; Hancock, 2003, 2004; Lieberman, 2022; Manza, 2000; Neubeck & Cazenave, 2002; Sears & Henry, 2005; Snowden & Graaf, 2019) and Whites' greater position of political influence in anti‐welfare states (Alesina et al, 2001; Manza, 2000; Neubeck & Cazenave, 2002)—especially in disproportionately African American, southern, anti‐welfare states (Acharya et al, 2018; Knuckey, 2017; Manza, 2000)—such that Whites' bias predominantly influences safety net policy and programming in those areas.…”
Section: Methodsmentioning
confidence: 99%
“…North Carolina may be particularly susceptible to second-generation barriers. Knuckey (2017) analyzed the 11 states of the old Confederacy and found that North Carolina had the second strongest relationship between racial resentment and Republican Party identification among Whites. 23 Critics of VIVA claim that policies requiring photo identification to vote, reducing early voting days, eliminating same-day registration, prohibiting of out-of-precinct voting, and eliminating preregistration are examples of second-generation barriers aimed at depressing the Black vote in North Carolina.…”
Section: Conceptual Framework and Identification Strategymentioning
confidence: 99%
“… 23 States using in the analysis conducted by Knuckey (2017) included Mississippi, Georgia, South Carolina, Virginia, Texas, Florida, Tennessee, Arkansas, Alabama, Louisiana, and North Carolina. North Carolina had the second strongest relationship between racial resentment and Republican Party identification behind Mississippi. …”
mentioning
confidence: 99%